DIGITAL MARKETING MODEL AND IMPULSIVE BUYING BEHAVIOR IN ONLINE PAY LATER SYSTEMS: A CASE STUDY IN THE MARKETPLACE - Indra Ade Irawan; Satria Yunas; Setiarini Setiarini (Jurnal Ekonomi, 2022)
The purpose of this study is to analyze and measure the effect of the Digital Marketing Model on the Online Pay Later System and analyze and measure the effect of Impulsive Buying Behavior on the Online Pay Later System. The population used in this study is the Online Pay Later System Users in the Depok City Region. The sampling technique in this study is the Convinience Sampling technique, data collection by distributing questionnaires to 150 respondents who are willing to fill out the questionnaire. The data that has been collected is processed by the method of multiple regression analysis. The results of this study indicate that the Digital Marketing Model has a significantly positive effect on the Online Pay later System, Impulsive Buying Behavior has a significantly positive effect on the Online Pay later System. The implication of this research is that online pay later system providers should provide more detailed information and understanding related to the advantages and risks as well as sanctions in the use of the online pay later system.